Board characteristics and sustainability report quality: Profitability as a moderating variable - Marfuah, Marfuah; Hamsyah, Erica Mariah Salma (Journal of Accounting and Investment, 2025)
Research aims: This research aims to determine the influence of board characteristics on the quality of sustainability reports and examine the role of profitability as a moderating variable in manufacturing companies in Indonesia.Design/Methodology/Approach: This study uses a quantitative approach. The sample was selected using the purposive sampling method, involving 24 companies and a total of 46 observations. The research hypotheses were tested using Moderated Regression Analysis (MRA).Research findings: The research provides empirical evidence that the size of the board of directors and the size of the audit committee have significant and positive effects on the quality of the sustainability report. However, the proportion of independent commissioners, the age of the members of the board of commissioners, gender diversity in the board of directors, the frequency of board of directors’ meetings, and the size of the audit committee do not significantly and positively affect the quality of the sustainability report. Profitability as a moderating variable was found to strengthen the influence of the proportion of independent commissioners on the quality of sustainability reports. However, profitability did not fortify the influences of the board of directors' size, the age of the board of commissioners, gender diversity in the board of directors, meeting frequency of the board of directors, and the size of the audit committee on the quality of the sustainability report.Theoretical contribution/Originality: This study shows that profitability moderates only the link between board independence and report quality, challenging the notion that financial performance uniformly strengthens governance. It refines Agency Theory by revealing the context-dependent nature of profitability’s moderating effect.Practical/Policy implication: For policymakers, the findings highlight the need to prioritize governance quality, such as audit committee expertise, over size. For companies, profitability should be leveraged by strengthening independent boards rather than expanding their size.Research limitations/Recommendations: This study focuses on Indonesian manufacturing firms, limiting generalizability. Future research should include cross-sector comparisons and examine qualitative aspects of board members, such as expertise.